Antioxidants, endothelial dysfunction, and DCS: In vitro and in vivo study - Wang, Q.; Mazur, A.; Guerrero, X.; Lambrechts, K.; Buzzacott, Peter; Belhomme, M.; Theron, M. (2015)
Copyright © 2015 the American Physiological Society. Reactive oxygen species (ROS) production is e well-known effect in individuals after an undersea dive. This study aimed to delineate the links between ROS, endothelial dysfunction, and decompression sickness (DCS) through the use of antioxidants in vitro and in vivo. The effect of A-acetylcysteine (NAC) on superoxide and peroxynitrite, nitric oxide (NO) generation, and cell viability during in vitro diving simulation were analyzed. Also analyzed was the effect of Vitamin A and NAC on plasma glutathione thiol and thiobarbituric acid reactive substances (TBARS), plasma angiotensin-converting enzyme (ACE) activity, and angiotensin-II and DCS morbidity during in vivo diving simulation. During an in vitro diving simulation, vascular endothelial cells showed overproduction of superoxide and peroxynitrite, obvious attenuation of NO generation, and promotion of cell death, all of which were reversed by NAC treatment. After in vivo diving simulation, plasma ACE activity and angiotensin-II level were not affected. The plasma level of glutathione thiol was downregulated after the dive, which was attenuated partially by NAC treatment. Plasma TBARS level was upregulated; however, either NAC or Vitamin A treatment failed to prevent DCS morbidity. During in vitro simulation, endothelial superoxide and peroxynitrite-mediated oxidative stress were involved in the attenuation of NO availability and cell death. This study is the first attempt to link oxidative stress and DCS occurrence, and the link could not be confirmed in vivo. Even in the presence of antioxidants, ROS and bubbles generated during diving and/or decompression might lead to embolic or biochemical stress and DCS. Diving-induced oxidative stress might not be the only trigger of DCS morbidity.